Estimating the Time to Do Nothing: Toward Next-Generation Models of Response Inhibition. (December 2022) - Bissett, Patrick G.; Poldrack, Russell A.
Controlled behavior requires response inhibition, which is a cognitive function that involves withholding action as goals change. Response inhibition is often assessed using the stop-signal paradigm, in which participants respond to most stimuli but periodically withhold their response when a subsequent stop signal occurs. The stop-signal paradigm rests on the theoretical foundation of the independent race model, which assumes a stop racer that races independently against a go racer; behavior is determined by which racer finishes first. We highlight work showing violations of the keystone independence assumption of existing stop models and discuss promising new models of response inhibition.